Optimizing crossflow humidifier -experimental insights towards sustainable innovations for societal benefit - Sampath Suranjan Salins; Shiva Kumar; S.V. Kota Reddy (International Journal of Sustainable Engineering)
In today’s world, minimising cooling and heating costs is essential, while maintaining thermal comfort remains a top priority. This study aims to construct a crossflow humidifier unit utilising wood shaving material with varying densities for evaporative cooling. Air and fluid were circulated in the crossflow, with the air Reynolds number varying from 30,557 to 55,003. The results reveal that the system achieved a maximum rate of evaporation of 0.4 g/s, & saturation efficiency of 79.23%, a coefficient of performance of 6.05, and a pressure drop of 87 Pa at a maximum power consumption of 210 W. All operating parameters were optimised to maximise the performance of the wood-shaving-based crossflow humidifier. The findings indicated that an air Reynolds number of 43,000 and a packing density between 490 and 530 kg/m3 resulted in optimal performance, with a power consumption of 176 W. Overall, the system was found to be sustainable, offering minimal costs, easy maintenance, and lower operating and power consumption.